GAMBARAN KESIAPAN PERANCANGAN SISTEM NAVIGASI PASIEN KANKER DI RUMAH SAKIT KANKER DHARMAIS - Suryani, Fitria; Djasri, Hanevi; Kusumaratna, Rina R (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2022)
Background: Cancer patient navigation is a coordinated assistance process that assists patients in overcoming barriers to timely and high-quality cancer care. Nonetheless, research on the design of an effective patient navigation system is still scarce. Objectives: To obtain an overview of the readiness of the navigation system for cancer patients at the Dharmais Cancer Hospital from the aspect of leadership policy, availability of resources, and assessing the knowledge level of navigators. Method: Case studies at the Dharmais Cancer Hospital were conducted from August to November 2022. A total of 13 informants involved in designing the cancer patient navigation system conductedin-depth interviews. Qualitative data were analyzed by the thematic analysis method. Quantitative data were obtained from field obser vations and document reviews using a modified checklist of the conformity of the American Cancer Society’s standard - cancer patient navigation design practices, as well as a closed questionnaire to assess eight navigators’ knowledge levels. Results: There are 15 components, each representing a different aspect of the design. The standards define four components that represent the leadership policy standpoint. All four requirements are met. Inconsistency in patient monitoring and the availability of approved SOPs were two of the seven resource availability components that were ineffective. The subjective navigator recruitment process is onecomponent that is unsuitable from the perspective of a navigator. The patient navigator candidate’s knowledge level is 35.12%, which is considered good.Conclusion: Only the leadership and policy aspects are fully met out of the 15 components representing three aspects of the design. Patient monitoring, ratification of activity SOPs, and the presence of an open navigator healing process and goals can all help to improve navigation system development.